2018
DOI: 10.2151/sola.2018-005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Relationships between Subtropical Marine Low Stratiform Cloudiness and Estimated Inversion Strength in CMIP5 Models Using the Satellite Simulator Package COSP

Abstract: Using the Cloud Feedback Model Intercomparison Project Observation Simulator Package (COSP) outputs, subtropical marine low stratiform cloud (LSC) amounts simulated in 12 Coupled Model Intercomparison Project phase 5 (CMIP5) models are robustly evaluated in terms of the relationship with the estimated inversion strength (EIS). The International Satellite Cloud Climatology Project (ISCCP) low-plus-middle cloud amounts with optical thickness > 3.6, corrected with the random-overlap assumption, are defined as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…This is closely linked to the development of so‐called marine inversions, which are initiated by the cooling effect of a large body of water on the warmer air masses above. As already mentioned, the marine inversions are an essential factor which controls the formation of the low stratiform clouds (Koshiro et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This is closely linked to the development of so‐called marine inversions, which are initiated by the cooling effect of a large body of water on the warmer air masses above. As already mentioned, the marine inversions are an essential factor which controls the formation of the low stratiform clouds (Koshiro et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, by restricting the vertical air mixing, the tropospheric temperature inversions play a crucial role in low-level cloud formation. A literature survey indicates a general consensus that there is a strong positive correlation between low-cloud cover and selected measures of inversion strength, such as the low-level stability and estimated inversion strength (Wood and Bretherton, 2006;Zhang et al, 2009;Naud et al, 2016;Galewsky, 2018;Koshiro et al, 2018). Owing to the relatively high albedo and cloud-top temperature, the low stratiform clouds have also a strong cooling effect on the Earth's radiative budget and thus influence on climate change feedbacks (Qu et al, 2015;Ceppi and Gregory, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed that global distributions of fog frequency and LWC are substantially different among climate models. It has been shown by numerous studies that cloud representation have a large spread even among state‐of‐the‐art climate models (e.g., Jiang et al, ; Koshiro et al, ; Nam et al, ; Nuijens et al, ; Su et al, ). Therefore, it is not surprising that fog representation also has a large diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Kawai et al (2017) developed an index for low-cloud cover, the ECTEI. This index is deduced from a criterion of cloud top entrainment (Randall, 1980;Deardorff, 1980;Kuo and Schubert, 1988;Betts and Boers, 1990;MacVean and Mason, 1990;MacVean, 1993;Yamaguchi and Randall, 2008;Lock, 2009) and includes information on both the vertical profile of temperature and that of water vapor. The definition of ECTEI is as follows:…”
Section: New Index For Low-cloud Covermentioning
confidence: 99%